Differences in Size Among Waterbird Eggs in Pulau Rambut: Some Preliminary Observations - Ani M Pakpahan (Media Konservasi, 1991)
Eggs of waterbirds (herons, egrets, ibises, and cormorants) are very similar in shape, dimension and appearance. All have an oval shape, about 5 cm long and 3 cm wide or slightly smaller. Although most author agree about the description of the texture (i.e., fine texture, smooth), the color description vary widely, depend on the authority. The egg color of these species have been described as pale bluegreen, greenish, bluish-white, greenish-white, and so forth.in Pulau Rambut, colonies of grey heron (Ardea cinerea), purple heron (A. cmerea), black-crowned night heron (Nycticornw nycticornw), great egret (Egretta alba), little egret (E. gozettn), cattle egret (Bubulcus ibis), cormorant(Phalacrocorur sp.) and glossy ibis (Plegadis falcinellus) nest in the same mangrove forest during January 1990. Very often nests of different species are mixed in the same tree and makes it difficult to identify the egg unless the parents are present.The objective of this study is to examine the size (weight, length, and width) and general appearance of 7 species of waterbircis nesting in Pulau Rambut during January 1990. This knowledge is especidly important when encountering an unidentified waterbird in the field. Moreover, if an egg is present in a nest, it can be used to identify the owner of the eggs and/or nest as well. This study is a part of a dissertation project on the characteristics of waterbirds' nests.